Genetic suppression demonstrates interaction of TonB protein with outer membrane transport proteins in Escherichia coli. - Bell, P E (1990)
Energy-coupled reactions of the Escherichia coli outer membrane transport proteins BtuB and Cir require the tonB product. Some point mutations in a region of btuB and cir that is highly conserved in TonB-dependent transport proteins led to loss of TonB-coupled uptake of vitamin B12 and colicin Ia, whereas binding was unaffected. Most other point mutations in this region had no detectable effect on transport activity. Mutations in tonB that suppressed the transport defect phenotype of these btuB mutations were isolated. All carried changes of glutamine 165 to leucine, lysine, or proline. The various tonB mutations differed markedly in their suppression activities on different btuB or cir mutations. This allele specificity of suppression indicates that TonB interacts directly with the outer membrane transport proteins in a manner that recognizes the local conformation but not specific side chains within this conserved region. An effect of the context of the remainder of the protein was seen, since the same substitution (valine 10----glycine) in btuB and cir responded differently to the suppressors. This finding supports the proposal that TonB interacts with more of the transport proteins than the first conserved domain alone.